Motives of Students for or Against the Practice of Physical Exercise and How They Are Related with the Climate in Physical Education Classes - Toro-Arevalo, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The main aim of the study was to investigate the reasons that motivate secondary school pupils to practise physical exercise, and how these motives are related to their perception of the climate in physical education classes. Participants: The sample consisted of 448 subjects, 36.8% girls and 63.2% boys, aged between 16 and 19 years (M = 17.61; SD = 0.96). The methodology was a de-scriptive cross‐sectional study. Two instruments were applied: self‐reporting by the pupils of their motives for practising physical exercise, and a questionnaire on their attitudes towards teachers’ behaviour and the physical education programme. The results showed that the strongest motive for the practice of physical exercise was “Prevention and positive health” (M = 5.29; SD = 1.45). In con-clusion, there is a weak correlation among the pupils’ motives for practising physical exercise and their perception of the climate in class. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.